Gestão de recursos tecnológicos: estudo de caso - (:unkn) unknown (Universidade Federal do Pampa, 2013)
Today, living without technological resources is practically unfeasible; however, the absurd number of non-environmentally friendly products is compromising our very existence by putting at risk the environmental balance. Aware that human activities interfere negatively with the environment, the study of technological resources is being treated with greater intensity, attracting the attention of many; as the 13th Cia Com Mec, which sensitized with the issue, makes the decision to collect and store technological products in the hope of reducing the disposal of these waste irregularly, since the municipality does not have this type of service. The objective of this work is to identify efficient practices in the management of technological waste, since the implementation of an electronic waste management system requires high investment, timely dedication, trained personnel, partnership with waste pickers association, infrastructure, there is no way to leave to mention, the importance of the population's awareness, then, it is fundamental to work the dissemination and environmental education throughout the city; elaborate project requesting the partnership of the municipal body, are just some of the many questions to be overcome. The interest demonstrated by the 13th CIA shows that the municipality can count on the support of this military unit in relation to environmental issues.
Technological resources management: a case study
Keywords: Resíduos eletrônicos; Resíduos sólidos; Gestão de resíduos; Electronic waste; Solid wastes; Waste Management; CNPQ::CIENCIAS BIOLOGICAS